2017
DOI: 10.3847/1538-4357/836/2/183
|View full text |Cite
|
Sign up to set email alerts
|

Was 49b: An Overmassive AGN in a Merging Dwarf Galaxy?

Abstract: We present a combined morphological and X-ray analysis of Was49, an isolated, dual-AGN system notable for the presence of a dominant AGN, Was 49b, in the disk of the primary galaxy, Was 49a, at a projected radial distance of 8kpc from the nucleus. Using X-ray data from Chandra, the Nuclear Spectroscopic Telescope Array, and Swift, we find that this AGN has a bolometric luminosity of L bol ∼ 10 45 erg s −1 , with a black hole mass of. Despite the large mass, our analysis of optical data from the Discovery Ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 104 publications
(137 reference statements)
5
33
0
Order By: Relevance
“…The velocities of the optical emission lines from the two nuclei differ by ∼70 km s −1 . The extreme luminosity of Was 49b is unusual for an AGN in the smaller galaxy of a minor-merger system (Secrest et al 2017). Was 49b is also radio-loud, and its radio emission is resolved in our GMRT 1.4 GHz continuum map.…”
Section: J1214+2931mentioning
confidence: 74%
“…The velocities of the optical emission lines from the two nuclei differ by ∼70 km s −1 . The extreme luminosity of Was 49b is unusual for an AGN in the smaller galaxy of a minor-merger system (Secrest et al 2017). Was 49b is also radio-loud, and its radio emission is resolved in our GMRT 1.4 GHz continuum map.…”
Section: J1214+2931mentioning
confidence: 74%
“…Indeed, only 0.1% of quasars are found in pairs with projected separations of tens to hundreds of kiloparsecs (e.g., Foreman et al 2009;Hennawi et al 2010), and until recently only a handful of confirmed dual AGNs with projected separations less than 10 kpc were known in the universe (e.g., NGC 6240: Komossa et al 2003;Mrk 463: Bianchi et al 2008;Arp 299: Ballo et al 2004;3C 75: Owen et al 1985; Radio Galaxy 0402+379: Rodriguez et al 2006;Was49: Moran et al 1992;Secrest et al 2017), all of which were discovered serendipitously. In the past few years, with the advent of large-scale optical spectroscopic surveys, more systematic surveys of dual AGNs have been possible.…”
Section: The Rarity Of Dual Agnsmentioning
confidence: 99%
“…We demonstrated in our previous study of interacting galaxies (Satyapal et al 2014) that both -> W W 1 2 0.5 and -> W W 1 2 0.8 color cuts produce qualitatively similar results. We note that hydrodynamic merger simulations that include radiative transfer predict that the -W W 1 2 color rises above 0.5 just before the stage of peak black hole growth, where star formation rates (SFRs) are high and where dual AGNs are expected to be found (L. Blecha et al 2017, in preparation; see also Snyder et al 2013;Roebuck et al 2016, for simulations of the mid-infrared spectral energy distribution with varying contributions of AGN and star formation activity), and that a color cut of -> W W 1 2 0.5 is actually more effective at finding dual AGN candidates than is the Blecha et al 2017, in preparation). We emphasize that the adopted color cut of -> W W 1 2 0.5 is optimized to provide the most inclusive sample of merger AGN candidates.…”
Section: Sample Selectionmentioning
confidence: 99%
“…NuS-TAR data allows us to uncover the reflection component of Was 49, that is not constrained with Chandra and Swift-BAT data alone. Was 49 NuSTAR spectrum has been analyzed also by Secrest et al (2017), finding bestfit photon index (Γ=1.6±0.1) and intrinsic absorption (N H =2.3…”
Section: +079mentioning
confidence: 99%